2017
DOI: 10.1080/14670100.2017.1408231
|View full text |Cite
|
Sign up to set email alerts
|

Surgical complications of cochlear implantation in a tertiary university hospital

Abstract: Cochlear implantation is a safe surgical technique for rehabilitation of patients with severe to profound hearing loss, associated with a low surgical complications rate. The majority of surgical complications can be managed with conservative measures or minimal intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 35 publications
0
15
0
3
Order By: Relevance
“… 16 Achiques MT has reported a prevalence of 11.38%. 17 While, Awad AH et al 18 reported complication rate of 10.43% with 6.75% minor and 3.68% major complications. Dodson KM et al reported a complication rate of 9.3%, with 59% related to device failure and 3 intracranial complications including two with minor dura leak which was repaired with fascia and one with acute hematoma treated by evacuation.…”
Section: Discussionmentioning
confidence: 97%
“… 16 Achiques MT has reported a prevalence of 11.38%. 17 While, Awad AH et al 18 reported complication rate of 10.43% with 6.75% minor and 3.68% major complications. Dodson KM et al reported a complication rate of 9.3%, with 59% related to device failure and 3 intracranial complications including two with minor dura leak which was repaired with fascia and one with acute hematoma treated by evacuation.…”
Section: Discussionmentioning
confidence: 97%
“…26,28 Late postoperative complications include failure or displacement of the device, facial nerve twitching, chronic ear infections, 26 abscess in the implant bed, rejection of the implant because of SSI, and stimulation of the tympanic nerve. 26,28 Nursing care plays a key role in the early detection and follow-up treatment of complications after CI surgery. 5,27 Postoperative meningitis may develop because of congenital anomalies in the cochlea and contamination of pathogens of the middle ear with CSF through the CI.…”
Section: Possible Complications Of CI Surgerymentioning
confidence: 99%
“…38 Compression of, or trauma to, the facial nerves may lead to facial nerve damage. 28 After the patient wakes, the nurse should check for asymmetry by asking the patient to extend his or her tongue and smile. Any facial twitching or loss of taste should be investigated.…”
Section: Possible Complications Of CI Surgerymentioning
confidence: 99%
See 2 more Smart Citations